Electric circuits a concise, conceptual tutorial - Zeng, Gengsheng Lawrence; Zeng, Megan (Springer, 2021)
This textbook serves as a tutorial for engineering students. Fundamental circuit analysis methods are presented at a level accessible to students with minimal background in engineering. The emphasis of the book is on basic concepts, using mathematical equations only as needed. Analogies to everyday life are used throughout the book in order to make the material easier to understand. Even though this book focuses on the fundamentals, it reveals the authors' deep insight into the relationship between the phasor, Fourier transform, and Laplace transform, and explains to students why these transforms are employed in circuit analysis. Written to be used as a “personal tutor” for a college student who is taking a lower level electric circuits course; Focuses on one concept per chapter, using numerous solved examples to make the presentation simple, concise, clear and to the point; Explains concepts from a “bird's-eye view” so readers can grasp how concepts fit into a larger context; Covers practical, hands-on topics, such as how to use a multimeter, how to use an oscilloscope, and how to use a power supply; Includes exercises at the end of each chapter with detailed, step-by-step solutions at the end of the book, making this an ideal tool for self-study.